Sing and Sing On: Sentinel Musicians and the Making of the Ethiopian American Diaspora - Kumar, Rakesh (International Library of African Music, 2023)
Review of "Sing and Sing On: Sentinel Musicians and the Making of the Ethiopian American Diaspora. Kay Kaufman Shelemay, 2022. Chicago: University of Chicago Press. 57 b/w illustrations, bibliography, index, 432 pages."
Keywords: Migration; Musicians; African diaspora; Music; Ethiopian American Diaspora; Sentinel Musicians; Diaspora Studies; Identity; African Music; Ethiopia